Psikoedukasi Pengenalan Beragam Emosi Kepada Siswa SDN 17 Tanjung Batu Ogan Ilir - amany, Talitha; arisandy, Desy (Lembaga Dongan Dosen, 2025)
Grade 2 students at SDN 17 Tanjung Batin the classroom learning process, children often exhibit behaviours such as crying, getting angry and upset for no apparent reason. These children appear to have difficulty in expressing their emotions in an appropriate way, so their emotions often appear suddenly and are difficult to control. The methods used are observation, interviews, games, education. The results of the community service obtained that psychoeducation on the introduction of various emotions to grade 2 students showed a positive influence in helping children recognise, understand, and express their feelings both verbally and non-verbally